Performance measurement of public hospitals through the integration of SWOT and balanced scorecard - Setiawannie, Yuli; Rahmania, Tiara (Jurnal Sistem dan Manajemen Industri, 2019)
Performance measurement is an essential factor for an organization to control the implementation of the strategy. The existing performance measurement system only evaluates financial performance. This study aims to propose the Key Performance Indicators (KPI) and measuring hospital performance with SWOT and BSC integration. Stages of research are determining internal and external factors with SWOT analysis, formulating alternative strategies, translating strategies into BSC perspective on strategic maps, determining performance indicators (KPI), KPI validation with AHP to obtain indicator weights for each view, and measuring hospital performance. Based on the results of the study, performance indicators (KPI) for hospitals based on the Balanced Scorecard perspective are six financial perspective indicators, two customer perspective indicators, four internal process perspective indicators, and five growth and learning perspective indicators. The internal process perspective is 90.43%, which means that the performance of the hospital is very healthy with the AA category, and learning 68.89% means that the performance of the hospital is very healthy with category A.